Contributing factors of clinical outcomes at 1 year post-diagnosis in early rheumatoid arthritis patients with tightly controlled disease activity in clinical practice: a retrospective study. Issue 2 (4th March 2021) - Kawashiri, Shin-ya; Endo, Yushiro; Okamoto, Momoko; Tsuji, Sosuke; Shimizu, Toshimasa; Sumiyoshi, Remi; Koga, Tomohiro; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; Nakamura, Hideki; Origuchi, Tomoki; et al.
Abstract: Objectives: To determine whether specific parameters contribute to clinical outcomes at 1 year post-diagnosis in early rheumatoid arthritis (RA) patients under the 'treat-to-target' strategy in clinical practice. Methods: We retrospectively analyzed 125 RA patients selected according to the following criteria; the patients' symptom duration was ≤6 months, and none had experience with DMARDs. We evaluated the patients' clinical disease activity at baseline and 1 year of treatment and the musculoskeletal ultrasound (MSUS)-detected synovitis activity at baseline. We performed an analysis to identify parameters that contribute to SDAI remission and the use of biologic/targeted synthetic (b/ts) DMARDs at 1 year post-diagnosis. Results: Forty-seven patients received b/tsDMARDs therapy, and 58 patients achieved SDAI remission at 1 year post-diagnosis. Rheumatoid factor positivity, low patient's/evaluator's global assessment at baseline, and methotrexate use at 1 year post-diagnosis were associated with SDAI remission. The baseline clinical disease activity and MSUS scores were not associated with SDAI remission. Anti-cyclic citrullinated peptide antibody positivity/high titer and high swollen joint counts or the presence of severe synovial hypertrophy at baseline were associated with the use of b/tsDMARDs therapy. Conclusion: The value of the expected poor-prognosis factors may be diminished by intensive therapy within the 'windows of opportunity'.